Use of biopsy and polymerase chain reaction for the diagnosis of cerebral toxoplasmosis in an HIV-positive female patient. A case report - Cámara-Reyes, Ramon Rolando (2024)
Infection by T. gondii is a significant cause of morbidity and mortality among people infected with HIV. The disease presents cerebral or encephalic involvement, especially among severely immunosuppressed patients. We present the case of HIV-infected pregnant women who presented with focal neurological manifestations during the second trimester of gestation. A single intracerebral lesion was found on brain imaging, and a brain biopsy and PCR identified toxoplasmosis. She improved clinically and radiographically after receiving proper treatment. The main contribution of our case is implementing a molecular test to define the diagnosis instead of a therapeutic challenge that may not make the diagnosis.